2019
DOI: 10.7322/jhgd.157754
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between motor performance and body composition of school adolescents

Abstract: Introduction:Motor coordination is a result of interactions between many body systems, producing accurate and balanced kinetic actions. The evaluation of motor performance levels in children and teenagers may conserve and improve health and life qualities. Body composition may interfere considerably in motor coordination, particularly in overweight and obese conditions. Objective: To analyse the relationships between motor performance and body composition in children. Methods:Motor coordination was evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Previously, similar findings were observed for non-athletic but healthyweight children. 20,24 On the other hand, various former examinations reported relatively higher values for the athletic population. 32,33 In their study, for instance, Vandorpe et al found 133.7 (±4.3) for elite female gymnast.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previously, similar findings were observed for non-athletic but healthyweight children. 20,24 On the other hand, various former examinations reported relatively higher values for the athletic population. 32,33 In their study, for instance, Vandorpe et al found 133.7 (±4.3) for elite female gymnast.…”
Section: Discussionmentioning
confidence: 91%
“…Previous research into gender differences is equivocal. [23][24][25][26]31 For example, Lopes et al examined the KTK performances of children aged 6-14 and noted the superiority of boys across all ages. 23 Notwithstanding, in line with the findings of the present study, Söğüt reported no significant gender effect in children between the ages of 6-14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A esse respeito, a Organização Mundial da Saúde -OMS (2016) alerta sobre a prevalência de disfunções motoras, também conhecidas por dispraxias, estimada entre 5 e 6% da população mundial e apresentadas pela Classificação Internacional de Doenças (CID-11) como 'Transtorno do Desenvolvimento da Coordenação Motora (ORGANIZAÇÃO, 2022). No Brasil, estudos evidenciam a preocupação acerca desta temática em crianças e adolescentes, onde o perfil motor (PM) identificado tem sido abaixo do esperado e a falta de vivências motoras agrava ainda mais essa realidade (GONÇALVES et al, 2021;MORES et al, 2019;RE et al, 2018;LUZ et al, 2018).…”
Section: Introductionunclassified
“…These students participated in activities based on their interest in joining the organization to develop their talents and hoped to gain more knowledge and experience and more friends (Mandey & Sahangggamu, 2014) [15]. Students who participate in school organization activities should not only be involved in activities because organizing requires seriousness and activeness from students so that students can actually learn democratic in organizing (Susanty & Baskoro, 2013), (Moraes et al, 2019) [16,17]. With the involvement of students in school organization activities are expected to provide significant benefits that produce students who are characteristic and leadership spirit such as courageous to lead, dare to make decisions, dare to express opinions, be willing to accept criticism, have a chivalrous attitude, advice, open, honest, responsible, respect opinions, maintain and appreciate togetherness, trust, fairness, discipline, and so forth (Sari et al, 2012) (Syahrial, Asrial, Husni Sabil, 2020) [18,19].…”
Section: Introductionmentioning
confidence: 99%